Radiations Induced Defects in electrode materials for energy storage devices. (February 2022) - Obodo, Raphael M.; Ramzan, M.; Nsude, Hope E.; Onoh, Edwin U.; Ahmad, Ishaq; Maaza, Malik; Ezema, Fabian I.
Abstract: Presently, scientists and scholars are faced with techniques of maintaining and elongating optimum performance of energy storage devices operating under radiations exposures. This review examine the effects of radiations such as ions, neutrons, laser, gamma etc. in electrodes of energy storage devices capacity loss, resistance increase, breakdown and poor performance as a result of radiation absorbed from surrounding environment. Radiations effect on electrodes of energy storage devices normally occur in various forms such ionization, atomic displacement, deformation, shift, impurity addition and loss in mass due to energy loss. An energy storage device that offers a reasonable energy and power densities nowadays includes batteries and supercapacitors. The world energy crisis has aggravated researchers' interest on ways of improving the working condition of these devices for betterment of humanity. This work studied energy storage devices, radiation that affects them and ways of managing radiation effects on energy storages devices for ideal performance. Highlights: Energy storage devices is key to operating electronics. Radiation disorganize atomic arrangements of materials. Long exposure to radiation affect electrodes of energy storage devices. Adequate care is needed to prevent radiation adverse effects on energy storage devices.